ΓΙΑΝΝΗΣ ΠΑΠΑΘΕΟΔΩΡΟΥ, «Αλλά τους τρελλούς τους κλείνουν εις τα φρενοκομεία». Υπερρεαλισμός, ψυχανάλυση και ηθικός πανικός στη δεκαετία του ’30 - Παπαθεοδώρου, Γιάννης (Σύγκριση/Comparaison/Comparison, 2022)
“Crazy people should be locked up in the asylum”. Surrealism, psychoanalysis and moral panics in ‘30s. In this paper, I discuss the ways in which the reception of psychoanalysis through surrealism diffused into the wider social discourse of popular culture during the interwar period. My central argument is that surrealism in Greece was connected to intellectual and mental illness. Thus, the concept of "scandal" is inscribed in the rhetoric of “moral panics”, that "paranoid modernism" causes. The polemic against surrealism emphasized its relationship with madness and the “margins” of the literary canon. On the other hand, this “cultural blockage” became a very productive field for surrealist poets to gain their own artistic autonomy.